The Year 2015: A Chronicle of Growing Authoritarianism. Issue 4 (3rd July 2016) - Petrov, N.
Abstract : Russian politics in 2015 was characterized by a continuation and strengthening of the lines of development first announced in the previous year. The chief trends in political development included a growing personalism and progressive deinstitutionalization of the Russian political system, the degradation of elections and of the judicial system, and the de facto dismantling of local self-government. The political elite underwent a radical shift in power, changing its overall configuration and enhancing the role of heads of the security forces. This coincided with the activation and strengthening of the apparatus of repression and an increase in pressure on regional elites, with continuing replacement of governors and of managers of state corporations.